2018
DOI: 10.22235/cp.v12i2.1693
|View full text |Cite
|
Sign up to set email alerts
|

Representaciones sociales del envejecimiento: un estudio con abuelas ancianas que cuidan de los nietos y abuelas que no

Abstract: Este trabajo tuvo como objetivo principal aprehender y comparar las representaciones sociales del envejecimiento entre abuelas que participan en la educación de los nietos y que no participan. La muestra caracterizó veinte mujeres abuelas, con edades entre 60 y 81 años, siendo que diez de ellas viven con los nietos y diez no viven y / o tienen poco contacto. Se utilizó la técnica de asociación libre de palabras, en la cual fue analizada por el software Iramuteq. A partir del análisis, se evidenció que las abue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The birth of a grandchild can impact both positively, bringing feelings of happiness and gratitude, and negatively, with the overload of care that grandparents may have. This is because the role of grandparents resembles that of parents, which can generate changes in such roles and even physical and emotional wear and tear as a result of dual motherhood with reduced physical capabilities (43) .…”
Section: Relationship Between Family Functionality and The Quality Of Life Of The Elderlymentioning
confidence: 99%
See 1 more Smart Citation
“…The birth of a grandchild can impact both positively, bringing feelings of happiness and gratitude, and negatively, with the overload of care that grandparents may have. This is because the role of grandparents resembles that of parents, which can generate changes in such roles and even physical and emotional wear and tear as a result of dual motherhood with reduced physical capabilities (43) .…”
Section: Relationship Between Family Functionality and The Quality Of Life Of The Elderlymentioning
confidence: 99%
“…In this perspective, a study (43) developed with 20 elderly women aged 60 years or more revealed that the grandmothers in close coexistence with their grandchildren demonstrated bigger challenges in the aging process whereas the elderly women who met their grandchildren sporadically attributed greater tranquility to old age. The authors suppose that the possible responsibilities of care on the part of grandmothers with their grandchildren compromise their satisfaction with aging (43) . Similarly, it happens when the elderly become the caregiver of their spouse, also becoming another factor capable of generating overload, illness, and guilt of the caregiver for the dependence of the partner (44) .…”
Section: Relationship Between Family Functionality and The Quality Of Life Of The Elderlymentioning
confidence: 99%